Membangun Moralitas Siswa SD dengan Program Daily Activities - Nuru Wakhidah; Vindi Isna; Agung Syaputra; Muhammad Nofan Zulfahmi (Lembag, 2025)
This study aims to explore and analyze how the Daily Activities program can contribute to building morality of elementary school students. The method used in this study is library research, which collects and analyzes various literature, articles, and academic sources related to the development of children's morality through daily activities at school. The results of the study show that a structured and planned Daily Activities program can be an effective means of instilling moral values, such as honesty, responsibility, and cooperation among students. In addition, activities that involve social interaction and experiential learning can increase students' moral awareness and form positive characters. This research is expected to contribute to the development of a more holistic and oriented educational curriculum that is oriented to the formation of student character, as well as a reference for educators in designing programs that support the development of morality in the school environment.